An evaluation of the internal validity of specific learning outcomes in phase II of a revised undergraduate medical curriculum - Cilliers, Francois Jakobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2001.